20th Biennial BDS Conference 2018 – Tour 4: Usk Reservoir. Issue 1 (29th January 2019) - Armour, Dougie; Walker, Alasdair
Abstract : This paper is an account of site visit (S4) to Usk Reservoir for the 20th Biennial BDS Conference 2018. Around 50 BDS delegates attended this visit to showcase some recent major spillway upgrade works. The paper describes the general background for the project as part of this tour, supplemented by accounts by the client and designer during the tour.